Oxford economic papers (Oxford : Clarendon Press, 1938)
Contains full text of articles, Oct. 1998- ; abstracts only, 1996-July 1998.
Title from title screen (viewed June 12, 2002).
Published: London : Oxford University Press, 1938-
Keywords: Economics -- Periodicals